Opettajien suhtautuminen tekoälyyn: Persoonallisuuspiirteiden ja motivaation vaikutukset teknologian hyväksymiseen ammatillisessa opetuksessa - Helin, Mereta (2024)
This thesis investigates how Finnish teachers utilize artificial intelligence (AI) in their teach-ing practices and which factors, such as personality and motivation, influence the acceptance and use of artificial intelligence. The study draws on technology acceptance models (UTAUT), personality models (Big Five), and motivation theories. Twenty teachers were interviewed for the study, and their perspectives were analyzed using qualitative content analysis. The results suggest that teachers' personality traits and motivational factors play a significant role in how they adopt new technology. Extraversion, openness to experience, and agreeableness supported the adoption of technology, while neuroticism was associated with stress related to its use. Additionally, motivational factors such as autonomy, curiosity, and social interaction emerged as key enablers of technology use. The study provides valuable insights into how teachers' individual needs and motivational drivers should be considered when introducing new technology. The findings support previous research on technology acceptance and offer new perspectives on how teachers' personalities and motivations influence their views toward artificial intelligence.